Does intrinsic motivation enhance motor cortex excitability?. (1st August 2016) - Radel, Rémi; Pjevac, Dusan; Davranche, Karen; d'Arripe‐Longueville, Fabienne; Colson, Serge S.; Lapole, Thomas; Gruet, Mathieu
Abstract: Intrinsic motivation (IM) is often viewed as a spontaneous tendency for action. Recent behavioral and neuroimaging evidence indicate that IM, in comparison to extrinsic motivation (EM), solicits the motor system. Accordingly, we tested whether IM leads to greater excitability of the motor cortex than EM. To test this hypothesis, we used two different tasks to induce the motivational orientation using either words representing each motivational orientation or pictures previously linked to each motivational orientation through associative learning. Single‐pulse transcranial magnetic stimulation over the motor cortex was applied when viewing the stimuli. Electromyographic activity was recorded on the contracted first dorsal interosseous muscle. Two indexes of corticospinal excitability (the amplitude of motor‐evoked potential and the length of cortical silent period) were obtained through unbiased automatic detection and analyzed using a mixed model that provided both statistical power and a high level of control over all important individual, task, and stimuli characteristics. Across the two tasks and the two indices of corticospinal excitability, the exposure to IM‐related stimuli did not lead to a greater corticospinal excitability than EM‐related stimuli or than stimuli with no motivational valence ( p s > .20). While these results tend to dismiss the advantage of IM at activating the motor cortex, we suggest alternative hypotheses to explain this lack of effect, which deserves further research.